Hydrogen peroxide as a clinical irrigation solution: A comparative study of the effect of hydrogen peroxide versus normal saline on the strength of the bone-cement interface - KELLY, DANIEL (IOS Press, 2007)
Hydrogen peroxide has been used for decades as an effervescent haemostatic agent in arthroplasty. Recently it has been shown to adversely affect the material properties of PMMA. We aim to assess whether any such deleterious effects are demonstrated in an experimental model which mimics the clinical use of hydrogen peroxide. Matched pairs of cancellous bone samples were treated with a swab soaked in either saline or a 3% solution of hydrogen peroxide, prior to manufacture of cement-bone constructs using Palacos or Simplex cement. Thirty pairs were then compared by subjecting them to a torsional shear force until failure and a further thirty pairs were tested to failure in tension. There was no significant difference between the mean torques to failure for the Palacos-peroxide group versus the Palacos-saline group, or the Simplexperoxide versus the Simplex-saline group (p=0.31 and 0.71 respectively). Similarly there was no significant difference between the mean tension loads to failure for the Palacos-peroxide group versus the Palacos-saline group, and the Simplex-peroxide versus the Simplex-saline group (p=0.79 and 0.23 respectively). We conclude that the use of hydrogen peroxide as an effervescent haemostatic agent has no detrimental effect on the mechanical integrity of the bonecement interface when compared to normal saline.
PUBLISHED
Keywords: Hydrogen Peroxide; Bone-Cement Interface; Arthroplasty